Respiratory complex I‐mediated NAD+ regeneration regulates cancer cell proliferation through the transcriptional and translational control of p21Cip1 expression by SIRT3 and SIRT7 - Masato Higurashi; Kazunori Mori; Hidetsugu Nakagawa; Momoko Uchida; Fumihiro Ishikawa; Motoko Shibanuma (Molecular Oncology)
The role of the electron transport chain (ETC) in cell proliferation control beyond its crucial function in supporting ATP generation has recently emerged. In this study, we found that, among the four ETC complexes, the complex I (CI)‐mediated NAD+ regeneration is important for cancer cell proliferation. In cancer cells, a decrease in CI activity by RNA interference (RNAi) against NADH:ubiquinone oxidoreductase core subunit V1 (NDUFV1) arrested the cell cycle at the G1/S phase, accompanying upregulation of p21Cip1 cyclin‐dependent kinase inhibitor expression. Mechanistically, a decrease in the NAD+/NADH ratio downregulated SIRT3 and SIRT7 function, which suppressed p21Cip1 expression at the translational and transcriptional levels, respectively, resulting in the upregulation of the antiproliferative molecule. Importantly, high expression levels of the core subunits of CI correlated with poor prognosis in patients with the hormone receptor(+)/human epidermal growth factor receptor 2(−) (HR+/HER2−) subtype of breast cancer. Therefore, NDUFV1 and SIRT3/7 have emerged as promising therapeutic targets against this breast cancer subtype.